Clinical profile and incidence of microvascular complications of childhood and adolescent onset type 1 and type 2 diabetes seen at a tertiary diabetes center in India. Issue 1 (29th May 2020) - Amutha, Anandakumar; Ranjit, Unnikrishnan; Anjana, Ranjit Mohan; Shanthi R., Coimbatore Subramaniam; Rajalakshmi, Ramachandran; Venkatesan, Ulagamathesan; Muthukumar, Subramaniapillai; Philips, Routray; Kayalvizhi, Sengottuvel; Gupta, Prasanna Kumar; Sastry, Nadiminty Ganapathi; Mohan, Viswanathan
Abstract: Aim: To study the clinical characteristics and incidence of microvascular complications among childhood and adolescent onset type 1 (T1DM) and type 2 diabetes (T2DM) seen at a tertiary care diabetes center in India. Methods: From our electronic medical records, we retrieved clinical and biochemical details of 4555 individuals with childhood and adolescent onset diabetes (diagnosed below the age of 20 years) seen between 1992 and 2017. T1DM was diagnosed if there was history of ketoacidosis or fasting C‐peptide <0.3 PMol/mL and stimulated C‐peptide <0.6 PMol/mL or if insulin treatment was required from the time of diagnosis. T2DM was diagnosed based on absence of ketosis, or fasting C‐peptide ≥0.6 PMol/mL and stimulated >1.0 PMoL/mL, or response to oral hypoglycemic agents for more than 2 years. We calculated the incidence rates of retinopathy (presence of at least one definite microaneurysm by retinal photography), nephropathy (urinary albumin excretion ≥30 μg/mg of creatinine) and neuropathy (vibration perception threshold ≥20 V) per 1000 person‐years of follow up. Results: Among the 4555 individuals with childhood and adolescent‐onset diabetes, 71.4% had T1DM, 19.5% T2DM and 9.1% other forms of diabetes. Age at first visit and duration of diabetes were significantly higher in T2DM when compared to T1DM. The age adjusted incidence of retinopathy was 52.9/1000 person years (Confidence Intervals [CI]: 42.9‐62.8) in T1DM and 49.8/1000 person years (CI 30.8‐68.8) in T2DM; nephropathy, 6.2 (CI 3.3‐9.0) and 13.8 (CI 5.6‐22.0); and neuropathy, 8.8(CI 3.6‐14.0) and 24.0 (CI 9.8‐38.2) in T1DM and T2DM, respectively. Conclusion: The incidence of microvascular complications is high among childhood and adolescent‐onset T1DM and T2DM and these calls for more aggressive control of diabetes.